The existence of borates in the waters of springs and rivers around Arequipa - Velasquez, Manuel A. (1918)
The discovery of borates in the waters of Jesus, performed by two of us (ESCOMEL and MALDONADO) in 1912 and the existence of borate deposits in the lagoon called "Salinas", indicated by Venegas in 1880 led us to think that these borates came probably these borate deposits. Moreover, the geological nature of the terrain and the altitude difference between the lagoon "Salinas" and nearby hot springs to Arequipa confirmed this origin hypothesis with the recent finding of borates in springs and rivers Arequipa, has found full verification.